Stinetinglers - Stine, R. L. (New York : Feiwel and Friends, 2022)
A collection of ten scary stories with brief introductions by the author.
Welcome to the In-Between -- Our little monsters -- Skin -- The ghost in the car -- The boy who heard screams -- Bugs -- How to change your life -- The bad side -- The hole in the ground -- The Monster-Maker.
Keywords: Horror tales, American; Children's stories, American; Short stories; Horror stories; Children's stories, American; Short stories; Juvenile Horror fiction; Short stories